Educational intervention for dental hygiene in preschool children from vulnerable contexts: self-efficacy, intention and perceived control by parents and children - Cavazos-Arroyo, Judith (2021)
Dental caries is one of the most prevalent chronic illnesses in early childhood, with repercussions on minors' quality of life. This vital stage constitutes an opportunity for children to acquire oral hygiene habits and control over them, especially in social vulnerability contexts. Objective: To analyze parents' beliefs about their ability to support their children in developing dental hygiene habits and children's beliefs about the acquisition of these habits before and after completing a dental hygiene development program. We established a quasi-experimental design with pre-test and post-test for two groups: parents and their preschool-age children participating in an educational program focused on developing dental hygiene habits in Mexico. We compared the habits, self-efficacy, intention and control on oral hygiene, through a paired t-test analysis. Results: The findings showed that the parents' intention to take action on their child's oral hygiene was higher than the behaviors carried out during the intervention. After the program, parents reduced their child's brushing supervision, and the children exhibited increased dental care behavior. Conclusions: We emphasize the relevance of carrying out continuous intervention work in the long term to empower children to control their oral health.